2018
DOI: 10.1016/j.aju.2017.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of postnatal hydroureter in determining the need for voiding cystourethrogram in children with high-grade hydronephrosis

Abstract: ObjectiveTo evaluate the utility of hydroureter (HU) to identify high-grade vesico-ureteric reflux (VUR) in patients with high-grade postnatal hydronephrosis (PH).Patients and methodsWe retrospectively reviewed patients’ charts that had antenatal hydronephrosis from 2008 to 2014. Patients were excluded if they presented with febrile urinary tract infection (fUTI), neurogenic bladder, posterior urethral valve, multi-cystic dysplastic kidney, and multiple congenital malformations. We reviewed postnatal ultrasono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
(41 reference statements)
1
4
0
Order By: Relevance
“…The increased UTI rate noted in our patients with hydroureteronephrosis is consistent with prior studies on congenital dilated ureter with published UTI rates between 19 and 50% [8,10,12]. PNH with ureteral dilation has been identified previously as an independent risk factor for UTI [6,8,9,18,19]. Similarly, CAP has been shown to be highly protective for patients with PNH and ureteral dilation >11 mm [6].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The increased UTI rate noted in our patients with hydroureteronephrosis is consistent with prior studies on congenital dilated ureter with published UTI rates between 19 and 50% [8,10,12]. PNH with ureteral dilation has been identified previously as an independent risk factor for UTI [6,8,9,18,19]. Similarly, CAP has been shown to be highly protective for patients with PNH and ureteral dilation >11 mm [6].…”
Section: Discussionsupporting
confidence: 91%
“…A recent prospective study on patients with prenatal hydronephrosis found that patients with non-refluxing primary megaureter (defined as ureteral diameter 7 mm or greater) had almost an 11 times higher risk of UTI [8]. Conversely, Hodhod et al (2018) demonstrated an increased UTI risk in prenatal hydronephrosis patients with hydroureter greater than 4 mm [9].…”
Section: Introductionmentioning
confidence: 99%
“…For low-grade isolated HN (SFU 1-2), the likelihood of VUR was reported to be about 2% and in high grade (SFU 3-4) ranged from 4% to 10%, regardless of whether it was unilateral or bilateral. [47][48][49] In the absence of infections, it is unclear if detecting reflux in these cases changes management dramatically. Conversely, if HN is persistently high grade (SFU 3 or 4), a nuclear renogram with furosemide may be considered after 8 weeks of age, and a pyeloplasty offered if obstruction is suspected.…”
Section: Isolated Hydronephrosis (Hn)mentioning
confidence: 99%
“…In terms of additional imaging, many question the need for a voiding cystourethrogram (VCUG) in this population. For low‐grade isolated HN (SFU 1–2), the likelihood of VUR was reported to be about 2% and in high grade (SFU 3–4) ranged from 4% to 10%, regardless of whether it was unilateral or bilateral 47–49 . In the absence of infections, it is unclear if detecting reflux in these cases changes management dramatically.…”
Section: Etiologies and Suggested Initial Managementmentioning
confidence: 99%
“…Ipsilateral hydronephrosis was graded 0 to 4 according to CTU images: grade 0-no caliceal or pelvic dilatation, grade 1-pelvic dilatation only, grade 2-mild caliceal dilatation, grade 3-severe caliceal dilatation and grade 4-caliceal dilatation accompanied by renal parenchymal atrophy. Grade 3 and grade 4 hydronephrosis were defined as high-grade hydronephrosis [6][7][8] .…”
Section: Hydronephrosis Classificationmentioning
confidence: 99%